FRAMING JOKO WIDODO DAN PRABOWO SUBIANTO DI HARIAN KOMPAS DALAM PEMILIHAN PRESIDEN 2019 - Prinisia Nurul Ikasari; Anisa Setya Arifina (Universitas Tidar, 2020)
In the context of campaigns and political interests, the image of individuals or political candidates can be created and supported by the public through the mass media. For this reason, it is very important and interesting to be able to see the frame or framing of the second pair of Joko Widodo-Ma'ruf Amin and Prabowo Subianto-Sandiaga Uno in the 2019 Election in the Kompas Newspaper mass media. The method used in this research is the analysis of media text content with data analysis through the Robert N. Entman framing model using the constructionism paradigm through qualitative research methods. The results showed Kompas conducted different framing on several news stories on the two Presidential Candidates in the 2019 election. The same framing occurred in several reports in the discussion of human rights issues. Key words: framing, Pemilu 2019, Mass Media, Politic.